TINJAUAN YURIDIS PENGELOLAHAN SAMPAH REGIONAL OLEH BADAN USAHA DI PROVINSI JAWA TIMUR MENURUT PERDA JAWA TIMUR NO 9 TAHUN 2022 TENTANG PENGOLAHAN SAMPAH REGIONAL - Suhendro, Muklis (LPPM Universitas Bina Bangsa, 2024)
Of course, waste processing cannot be carried out by the East Java Provincial Government. Therefore, several business entities are needed to take part in processing waste in East Java. In order for cooperation between the East Java Provincial Government and several business entities to run, of course regulations must be created to ensure legal certainty for both parties. Waste Management is a systematic, comprehensive and sustainable activity that includes reducing and handling waste. Waste processing is one activity that can reduce the high rate of waste accumulation. In reducing waste through waste processing, the role of business entities and the Government is necessary, and there needs to be regulations governing this cooperation to provide legal certainty. In the central level legislation, in general, there are two regulations that regulate waste processing by business entities. Firstly, material regulations, which are regulated in Law no. 18 of 2008 concerning Waste Management. This regulation provides legality for the Government to cooperate in waste processing. The second regulation is the Formill regulation which is regulated in the Government Regulation of the Republic of Indonesia Number 81 of 2012 concerning Management of Household Waste and Similar Types of Household Waste. Where in this regulation there are three articles that regulate waste processing by Business Entities, including: partnerships between Business Entities and the Government Development and application of technology; and Guidance on waste processing by Business Entities. The East Java Regional Regulation Number 2 of 2022 concerning Regional Waste Processing regulates 6 things regarding waste processing by Business Entities, including: Financing the organization of waste processing; Environmental impact control; the legality of government cooperation with business entities that carry out waste processing; Cooperation mechanisms; supervision of the implementation of waste processing by business entities; and Sanctions